Partisipasi Orang Tua Dalam Mendorong Pendidikan Anak Di Desa Talaga Kecamatan Ibu Selatan Kabupaten Halmahera Barat Pasca Pandemic Covid-19 Tahun Ajaran 2020-2021 (Universitas Khairun, 2022)
The background in this study is the role of parents in encouraging children's education during the online learning period after the Covid-19 pandemic. The research objectives: (1). to find out the form of parental participation in encouraging children's education in Talaga village after the Covid- 19 pandemic for the 2020-2021 academic year. (2). to find out what factors influence parents to encourage children's education in Talaga village after the Covid-19 pandemic for the 2020-2021 Academic Year. The research method used is a qualitative and descriptive approach. The data collection techniques are observation, interviews and document analysis. Sources of data used in this study are primary data and secondary data. While the research subjects are parents of students and students. Furthermore, researchers can describe the results of this study as follows: (1). Forms of Parental Participation in Encouraging Children's Education in Talaga Village after the Covid-19 Pandemic for the 2020-2021 Academic Year that in the implementation of education, the role of parents is very necessary. Parents are the first and foremost parties who will always control and supervise the education process of their children. Not only that, the role of parents is far more important in education, namely being a motivator for their children. The role of parents in education for their children includes three things, namely Motivation, Guiding, and Attention. (2). Factors Influencing Parents to Encourage Children's Education in Talaga Village after the Covid-19 Pandemic for the 2020-2021 Academic Year is the enthusiastic attitude of parents in good relations with children for more efficient learning. parental participation in terms of education, occupation, and the age of parents who are different also has an impact on increasing student interest and learning achievement. Parental involvement is very important because it will have a positive effect on the success and progress of children's education. The relationship between parents and schools will be able to gain knowledge and experience from schools/teachers in terms of their children's education.Keywords: Participation, Parents, Education